2019
DOI: 10.1002/arch.21543
|View full text |Cite
|
Sign up to set email alerts
|

Changes in immune responses of Helicoverpa armigera Hübner followed by feeding on Knotgrass, Polygonum persicaria agglutinin

Abstract: There is no study implying the effect of plant lectins on insect immune elements in both challenged and nonchallenged conditions with entomopathogenic agents. Lectins may bind to immune receptors on the surface of insect hemocytes, thus inducing or even disabling common immune functions including hemocyte counts, nodulation/encapsulation, phenoloxidase activity, and synthesis of antimicrobial peptides. In the present study, effect of Polygonum persicaria L. agglutinin (PPA) on immune responses of Helicoverpa a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…This reduction in blood cell numbers may be attributed to cellular lysis (Lu et al, 2011). The decreased number of total cells under cadmium excess is an indication of lack of metallothionein production (Roesijadi et al, 1997; J. Yang et al, 2011) or could be related to a disturbance in hemopoietic organs that are the source of haemocyte production (Rahimi et al, 2019). H. Wu et al (2022) found that Cd stress significantly reduced the number of haemocytes in a model organism, L. dispar larvae.…”
Section: Discussionmentioning
confidence: 99%
“…This reduction in blood cell numbers may be attributed to cellular lysis (Lu et al, 2011). The decreased number of total cells under cadmium excess is an indication of lack of metallothionein production (Roesijadi et al, 1997; J. Yang et al, 2011) or could be related to a disturbance in hemopoietic organs that are the source of haemocyte production (Rahimi et al, 2019). H. Wu et al (2022) found that Cd stress significantly reduced the number of haemocytes in a model organism, L. dispar larvae.…”
Section: Discussionmentioning
confidence: 99%
“…The insect's innate immune system embraces the cellular and humoral responses in which cell‐mediated immunity is performed particularly by hemocytes (Takov et al, 2020) through phagocytosis, nodulation, encapsulation, and melanization of invaders (Dubovskiy et al, 2016). Although the effects of tea seed saponin on insect immune responses have not been studied, there are some pieces of evidence suggesting that plant extracts such as azadirachtin (Azambuja et al, 1991), Artemisia annua L. (Asterales: Asteraceae) extracts (Zibaee & Bandani, 2010), and Polygonum persicaria lectins (Rahimi et al, 2019) negatively affect insect immune responses. Furthermore, De Geyter et al (2012) confirmed that saponins exert cytotoxic effects through fast and stringent permeation of insect cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Insects defend themselves by two methods against foreign bodies, a general method (i.e., cuticle and chemicals involve in defending insects) and the second one involving cellular and humeral responses ( Beckage, 2011 ; Dubovskiy et al, 2016 ; Rahimi et al, 2019 ). The plant products are capable of indulging in both of them and thus weakening the insects and make them susceptible to various diseases and parasites ( Veyrat et al, 2016 ; Gasmi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%